2022
DOI: 10.1002/agr.21778
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral framing and consumer acceptance of new food technologies: Factors influencing consumer demand for active packaging

Abstract: We examine consumer willingness to pay (WTP) for foods packaged using active packaging which can be used to improve quality, shelf life, or safety of a range of products, potentially reducing the use of food additives (preservatives) and food waste. We administer an experimental survey of US food consumers (n = 2325) with five treatments. The surveys include contingent valuation exercises to assess consumer WTP for six products in active packaging relative to conventional packaging. We find that consumer accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Given the lack of information regarding consumer perceptions of native plants and the diverse benefits of native plants, a cluster analysis has the potential to identify and provide a better understanding of different customer segments and factors that motivate consumer interest in native plants. Previous studies used a cluster analysis to address consumer segmentation for chicken products (Bannor et al 2022), food consumption and purchase patterns (Bond et al 2008;Larson 2004), fresh fruits (Torres et al 2020), gene-edited foods (Paudel et al 2023), and new food packaging technologies (Just and Goddard 2023). We used the factors in a cluster analysis to group people by similar perceptions so we could estimate the market potential for segments that are more receptive to native plants and which types of marketing messages (e.g., wildlife friendly, availability) may resonate better with them.…”
Section: Methodsmentioning
confidence: 99%
“…Given the lack of information regarding consumer perceptions of native plants and the diverse benefits of native plants, a cluster analysis has the potential to identify and provide a better understanding of different customer segments and factors that motivate consumer interest in native plants. Previous studies used a cluster analysis to address consumer segmentation for chicken products (Bannor et al 2022), food consumption and purchase patterns (Bond et al 2008;Larson 2004), fresh fruits (Torres et al 2020), gene-edited foods (Paudel et al 2023), and new food packaging technologies (Just and Goddard 2023). We used the factors in a cluster analysis to group people by similar perceptions so we could estimate the market potential for segments that are more receptive to native plants and which types of marketing messages (e.g., wildlife friendly, availability) may resonate better with them.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows that consumers' acceptance of MAP, VP, AP, and IP is well known [22][23][24][25]27,[29][30][31][32][33]. The misalignment between the lack of knowledge of the impact of packaging technologies on food freshness and the acceptance of these technologies has resulted from the latter being assessed after consumers were provided with written or verbal information on the packaging technologies right before responding [23,27,31]. However, consumers' acceptance of a packaging technology does not guarantee its purchase.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having the intention to buy, consumers must be willing to pay more for packaging technologies that reduce food waste, because they come at an additional cost. Due to these technologies' ability to extend food shelf-life, some research presented in Table 1 has found that consumers are prepared to pay more for MAP [25], AP and IP [24], AP [31,33], and VP [10]. However, other researchers have found the opposite [22,26,27,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the early research mainly adopted the scenario hypothesis experiment method to evaluate consumer preferences for the packaging functions (Bieberstein et al, 2013;Joutsela et al, 2017;Just and Goddard, 2022), but ignored that quality perception bias, defined by the difference between perceived quality and true quality, can be a key source hindering positive WTP values when conducting the method. Some studies have proved that perception bias exists widely among humans, and a large proportion of consumers hardly decide by fully optimizing (Allcott et al, 2022).…”
Section: Introductionmentioning
confidence: 99%